Alobar Holoprosencephaly with Cebocephaly in a Neonate Born to an HIV-Positive Mother in Eastern Uganda - Sikakulya, Franck Katembo; Kiyaka, Sonye Magugu; Masereka, Robert; Ssebuufu, Robinson (Case Reports in Otolaryngology, 2021)
Background. Holoprosencephaly (HPE) is a rare cerebrofacial abnormality resulting from the complete or partial failure of the diverticulation and cleavage of the primitive forebrain. It has an incidence at birth of 1:16000. Case Presentation. We report a case of a 2600 g newborn female delivered by an HIV-infected mother in whom an antenatal ultrasound scan at 34 weeks’ gestation reported features of fetal alobar holoprosencephaly. The neonate was born with cebocephaly, a monkey-like head, and did not survive for more than 30 minutes following delivery by caesarian section despite oxygen therapy. Conclusion. Alobar HPE with cebocephaly remains incompatible with life. In this resource-limited setting, the diagnosis was made clinically, and only an ultrasound scan was performed to confirm the diagnosis. Chromosomal analysis could have given more information.